Do Bioinoculants Affect Resident Microbial Communities? A Meta-Analysis - Cornell, Calvin; Kokkoris, Vasilis; Richards, Andrew; Horst, Christina; Rosa, Daniel; Bennett, Jonathan A.; Hart, Miranda M. (Frontiers in Agronomy, 2021)
There is a global industry built upon the production of ‘bioinoculants’, which include both bacteria and fungi. The recent increase in bioinoculant uptake by land users coincides with a drive for more sustainable land use practises. But are bioinoculants sustainable? These microbes are believed to improve plant performance, but knowledge of their effect on resident microbial communities is scant. Without a clear understanding of how they affect soil microbial communities, their utility is unclear. To assess how different inoculation practises may affect bioinoculant effects on soil microbial communities, we surveyed the existing literature. Our results show that bioinoculants significantly affect soil microbial diversity and that these effects are mediated by inoculant type, diversity, and disturbance regime. Further, these changes to soil microbes affect plant outcomes. Knowledge that these products may influence crop performance indirectly through changes to soil microbial diversity attests to the importance of considering the soil microbiome when assessing both bioinoculant efficacy and threats to soil ecosystems.